Confounding social and mating systems predictably lead to biased results when examining the evolution of cooperative breeding in cichlids: A response to Tanaka et al. (10th May 2019) - Dey, Cody J.; O'Connor, Constance M.; Wilkinson, Holly; Shultz, Susanne; Balshine, Sigal; Fitzpatrick, John L
Abstract: In 2017, we demonstrated that transitions to cooperative breeding in Lamprologine cichlid fishes were not related to a species' social mating system (Dey et al. 2017. Nature Ecology & Evolution, 1, 137). This contrasted previous evidence that monogamy (and a low degree of promiscuity) promoted transitions to cooperative breeding in other taxa. Recently, Tanaka et al. (2018. Ethology, 124, 777–789) critiqued our study and argued that a re‐analysis of the data shows transitions to cooperative breeding are promoted by non‐monogamous mating systems. Here, we show that Tanaka et al.'s critique contains numerous inaccuracies. In addition, we show that the results put forth by Tanaka et al. emerge only under the extreme scenario in which all cooperative breeding species are classified as non‐monogamous, which we argue arises because Tanaka et al. confound social systems and mating systems. While we agree that there is uncertainty regarding the mating system of some Lamprologine species, we argue this uncertainty was sufficiently addressed through the extensive sensitivity analyses conducted in our original study.